EDUKASI PENERAPAN IRIGASI TETES SEDERHANA PADA BUDIDAYA TANAMAN PAKCOY DI POLYBAG - Lolita Endang Susilowati; Isnaniar Rahmatul Azizah; Siti Azira Zilfida; M. Thoriq Jihadul Ilmi; Hayatun Nisa; Depi Tamala; Megawati Iskandar Putri; Alfrisa Wijayanti; Ayu Hikmatullaela Novesa; Ade Guswan Pratama; Furqon Adam; Lisa Umami (Universitas Mataram, 2023)
The issue of water scarcity in several areas of Indonesia, especially in Desa Kidang, has hindered the utilization of home garden land for cultivation, particularly of food crops like vegetables. In Desa Kidang, there are numerous unused plots of land. To address this problem, a simple drip irrigation system has been implemented as a solution to conserve water and time in plant irrigation. The objective of this activity is to enhance water usage efficiency in the cultivation of pakchoy plants through the use of a simple drip irrigation method. This system ensures optimal water usage in plant growth. The implementation of this project involves location surveys, discussions with partners, installation of the drip irrigation system, the cultivation of pakchoy plants, monitoring, and evaluation. As a result, the drip irrigation system has been able to save water by 50-70%. After the installation, caring for pakchoy plants becomes more efficient in terms of watering. Nevertheless, consistency in maintenance remains necessary to combat threats such as caterpillar infestations. Water usage efficiency through simple drip irrigation is crucial, especially in the cultivation of pakchoy, because, in addition to water conservation, it facilitates automatic watering and enhances plant production yields.